Pembuatan Aplikasi Sistem Informasi Manajemen Sekolah Untuk Layanan Penerimaan Peserta Didik Baru - Zulfikar Sembiring; Susilawati Susilawati; Muhathir Muhathir (Universitas Medan Area, 2020)
One of the education problems in this country is the zoning policy in the new student admission system (PPDB). This is in accordance with the policy of the Ministry of Education and Culture (Kemendikbud) in 2016 which began with the use of zoning for the administration of national exams. Then in 2017 the zoning system was implemented for the first time in implementing PPDB, and was refined in 2018 through Permendikbud Number 14 of 2018. The first problem faced is the zoning system organized by State Junior High Schools in Medan and the Education Office which still causes unrest for the community, especially parents, where the implementation has not been carried out in a transparent manner, both the number of prospective students who have registered at the school and the scoring system based on distance, the achievement of prospective students and the transfer of parents' duties. The second problem is the system for announcing the acceptance of prospective students who have passed a certain school is not generally published. The solution offered to deal with problems that occur to partners is by transferring science and technology in the form of management information system-based applications and services to partners in the form of a new student admission information system (PPDB), training related to the use of the PPDB system, and assistance to partners. . The result of this community service program is to increase insight and knowledge of skills for partners in optimizing the use of information systems and information technology to support PPDB operational activities, improving partners' skills and abilities in using school service management applications designed to facilitate the school PPDB process and implementation of PPDB. which is organized by schools and education offices to become more transparent to the public.